A review of the leafuopper genus Jikradia with descripíions of four new spedes (Homoptera: Cicadellidae) - Godoy, Carolina (1998)
The genus Jikradia Nielson extends from eastern North America to Central America and the Galapagos Islands. Four additional new species are described and ilustrated: J. mexicana (Mexico) J. ¡onga (Costa Rica, Guatemala, Mexico), J. zurquiensis (Costa Rica) and J. lizanoi (Costa Rica). J. mexicana general color is ochraceous; the aedeagus without seta-like spine. J. ¡onga, general color is light ochraceous; the aedeagus with long seta-like process subapically with three spine-like setae opposite to single subapical seta. J. zurquiensis, general color brown; aedeagus with single seta-Iike process subapically with three small spine-like setae basad of single subapical setae on the opposite lateral margin of aedeagus. J. lizanoi, general color brown; aedeagus asymmetrical, long, narrow, tube-like, in lateral aspect with sharply pointed apex, with two long seta-like processes subapically with four spine-like setae. A revised key to al! known species, and subspecies, based on male genitalia, is a1so presented.